2022
DOI: 10.3390/jcm11051427
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Functional Changes of Meibomian Glands in Pediatric and Adult Patients with Allergic Conjunctivitis

Abstract: Allergic conjunctivitis (AC) is one of the most common ocular disorders in clinical practice and is associated with meibomian gland dysfunction. This study aimed to explore the morphological and functional changes of meibomian glands (MGs) in pediatric and adult patients with AC and to analyze their potential predictors. In our prospective, observational cohort study, a total of 59 patients with AC were enrolled, with 30 patients aged ≤16 years in the pediatric group and 29 patients in the adult group. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…MG grade was classified according to the previous standard considering both MG area and distortion (Table 1). [21][22][23][24] The upper MG means MGs seen within the everted upper tarsal plate. Similarly, the lower MG was captured in the lower one.…”
Section: Examination and Image Analysismentioning
confidence: 99%
“…MG grade was classified according to the previous standard considering both MG area and distortion (Table 1). [21][22][23][24] The upper MG means MGs seen within the everted upper tarsal plate. Similarly, the lower MG was captured in the lower one.…”
Section: Examination and Image Analysismentioning
confidence: 99%
“…The meiboscore were graded as: 0, no loss of MGs; 1, less than one-third loss of glands; 2, one-third to two-thirds loss of glands; and 3, more than two-thirds loss of glands. The total meiboscore of the upper and lower eyelids ranged from 0-6 [30][31][32]. Conjunctiva redness was assessed by automated objective evaluation of the high magnification digital imaging according to the proprietary JENVIS grading scale from 0 to 4 [12].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In recent years, with the increase in research on dry eye in children and meibomian gland dysfunction (MGD), it has been found that a variety of diseases may be related to dry eye in children and MGD, such as allergic conjunctivitis, blepharitis and refractive error [3][4][5]. However, it is unknown whether epiblepharon is related to dry eye in children and MGD.…”
Section: Introductionmentioning
confidence: 99%